2012
DOI: 10.1097/aud.0b013e31825069e8
|View full text |Cite
|
Sign up to set email alerts
|

Generational Differences in the Reporting of Tinnitus

Abstract: Objectives Recent research suggests that hearing impairment is declining among older adults compared to earlier generations of the same age. Tinnitus is often associated with hearing impairment, so one might hypothesize that the prevalence of tinnitus is declining in a similar manner. The purpose of this study was to utilize multi-generational data with repeated measures to determine if the prevalence of tinnitus is declining among more recent generations. Design Using data from the Epidemiology of Hearing L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 16 publications
1
37
0
4
Order By: Relevance
“…This assumption is supported by findings of Nondahl et al [31] who showed that younger American people report a higher prevalence of behaviorally influenced tinnitus than elderly. The main behavioral factors include PMP, MP3 and/or MP4 and exposure to noise during night-outs.…”
Section: Discussionmentioning
confidence: 54%
“…This assumption is supported by findings of Nondahl et al [31] who showed that younger American people report a higher prevalence of behaviorally influenced tinnitus than elderly. The main behavioral factors include PMP, MP3 and/or MP4 and exposure to noise during night-outs.…”
Section: Discussionmentioning
confidence: 54%
“…The tendency over time was therefore a shift from pronounced to slight-moderate problems. Nondahl et al (2012) have reported an increasing prevalence of tinnitus in more recent generations of adults. In the present study, there was an increasing prevalence of tinnitus, both often/always and sometimes, for men belonging to cohort 6.…”
Section: Discussionmentioning
confidence: 97%
“…The estimated prevalence in the general population is about 10-15% [Langguth et al, 2013] and is expected to increase in the future [Nondahl et al, 2012;Gilles et al, 2013]. Tinnitus can be extremely bothersome, which may lead to depression and serious problems in daily life [Turner et al, 2007].…”
Section: Introductionmentioning
confidence: 99%